Mystical Knowledge and its Evaluative Criteria - Murtaza Waiz Jawadi (حکمت اسرا, 2011)
Some of the theoretical and practical slips in the realm of mysticism stem from an incorrect exposition of mystical knowledge and the criteria used to evaluate it. The article aims to prevent such errors by expounding mystical knowledge—its distinction from all other fields of knowledge and the way it should be used to reach reality, as well as the criteria of its validity.